2006
DOI: 10.1007/s00405-006-0152-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngocutaneous fistula following total laryngectomy: a single institution’s 10-year experience

Abstract: The etiology of postoperative pharyngocutaneous fistula (PCF) formation following major head and neck surgery is multifactorial and the incidence varies greatly. We reviewed retrospectively the records of 108 consecutive patients who underwent a total laryngectomy during the period from December 1992 to December 2002 at the Helsinki University Central Hospital, Helsinki, Finland. PCF occurred postoperatively in 19 (18%) patients. Two additional patients (2%) developed a PCF later than 30 days after laryngectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
65
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 15 publications
10
65
1
1
Order By: Relevance
“…In a recent study, Benson et al (5) reported the incidence as 34%. Our incidence of PCF (20.2%), which is still high, lies within the mid-range of previous series (1,(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a recent study, Benson et al (5) reported the incidence as 34%. Our incidence of PCF (20.2%), which is still high, lies within the mid-range of previous series (1,(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 86%
“…Although this opinion has many justifications, the early primary surgical closure of an existing PCF is not always easy and successful. According to our experience, as some PCFs spontaneously close with appropriate treatment, our initial approach was conservative treatment, as reported in other studies (7,13,14). However, if 2 weeks of conservative treatment fails, surgical intervention is required to attempt to close the fistula.…”
Section: Discussionmentioning
confidence: 69%
“…Post-surgical TPF or pharyngocutaneous fistulas occur within 30 days after surgery in majority of the cases and tend to close spontaneously [8,15]. Once radiochemotherapy has been conducted, the spontaneous closure of such fistulas becomes less common and surgical approaches have to be considered [25].…”
Section: Discussionmentioning
confidence: 98%
“…La fístula faringoesofágica está ampliamente descrita como complicación postoperatoria de la cirugía de la columna cervical a través de un abordaje anterior, en el que es necesario disecar el espacio prevertebral, muy próximo a la cara esofágica posterior 6 , y en las laringuectomías, adyacentes a la cara anterior del esófago 7 . Sin embargo, la lesión faringoesofágica es un hecho inusual en la cirugía paratiroidea, ya que la cara lateral del esófago está teóricamente lejos del campo quirúrgico de la paratiroides.…”
Section: Discussionunclassified